2015
DOI: 10.1007/s11356-015-4615-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gasoline distributions within petrol stations: spatial and seasonal concentrations, sources, mitigation measures, and occupationally exposed symptoms

Abstract: We measured levels of VOCs and determined the distributions of benzene concentrations over the area of two petrol stations in all three seasons. Using the concentrations and sampling positions, we created isoconcentration contour maps. The average concentrations ranged 18-1288 μg m(-3) for benzene and 12-81 μg m(-3) for toluene. The contour maps indicate that high-level contours of benzene were found not only at the fuel dispenser areas but also at the storage tank refilling points, open drainage areas where g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Regarding PPE, the use of boots was predominant, corroborating with other studies [23], while additional skin and inhalation protection equipment was reported only by some workers. Benzene and other organic compounds present in gasoline are absorbed when in contact with the skin and pass into the bloodstream; if a workman has a cutaneous lesion or wound the benzene absorption may be faster and may cause the same damages as occur by inhalation [27].…”
Section: Resultssupporting
confidence: 88%
“…Regarding PPE, the use of boots was predominant, corroborating with other studies [23], while additional skin and inhalation protection equipment was reported only by some workers. Benzene and other organic compounds present in gasoline are absorbed when in contact with the skin and pass into the bloodstream; if a workman has a cutaneous lesion or wound the benzene absorption may be faster and may cause the same damages as occur by inhalation [27].…”
Section: Resultssupporting
confidence: 88%
“…An important class of VOCs is the suite of BTEX (benzene, toluene, ethylbenzene, m/pxylene, and o-xylene) species, which have been the focus of many toxicological studies (Fazlzadeh Davil et al, 2011; Halliday, 2016; Hazrati et al, 2016a, 2015; Marć et al, 2016; Rad et al, 2014; Sairat et al, 2015). Ideal regions to study BTEX emissions and impacts include ‘hot spots’, which are typically urban areas where ambient levels significant exceed those of surrounding remote areas (Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their sources, including in this work’s study region, include vehicular exhaust, gas stations, industrial activity, landfill sites, municipal solid waste (MSW) stations, and combustion for domestic heating (Bruno et al, 2008; Carrieri et al, 2006; Chiriac et al, 2007, 2011; Correa et al, 2012; Durmusoglu et al, 2010; Jiang et al, 2017; Kim et al, 2008; Kountouriotis et al, 2014; Marć et al, 2016; Sairat et al, 2015; Terrés et al, 2010; Wu et al, 2006; Xiong et al, 2016). Past work has shown that more than 45% of total VOC emissions, such as for benzene and toluene, in Mexico City, the United Kingdom, and Los Angeles stemmed from gas stations, evaporation of petrol, and motor vehicle emissions (Correa et al, 2012; Durmusoglu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Petrochemical hydrocarbons, including BTEX compounds, are known as an indicator for exposure to volatile organic compounds as well as petroleum compounds [9]. Contact with BTEX compounds can occur through eating (using water contaminated with BTEX), inhalation of contaminated air, or adsorption through the skin [10]. Crude-oil-soluble derivatives and refined products include various types of toxic compounds for a wide range of plants and marine organisms.…”
Section: Introductionmentioning
confidence: 99%